2005
DOI: 10.1111/j.1365-2427.2005.01401.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria and algae in stream periphyton along a nutrient gradient

Abstract: 1. Stream riffles in southern Ontario and western Quèbec were sampled for biomass (58 stations from 51 streams) and production (22 stations from 21 streams) of algae and bacteria in periphyton to test the hypothesis that bacteria in benthic biofilms compete with algae for nutrients. 2. Algal and bacterial biomass were positively correlated, as were algal and bacterial production. Bacterial production was also positively correlated to algal and bacterial biomass, but the relationship was not significant. The ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
59
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(68 citation statements)
references
References 37 publications
7
59
1
1
Order By: Relevance
“…Biofilm turnover for environments -including decaying leaf litter, streams, mesocosm wetlands and tropical coastal lagoons -range from ~0.02 to 4000% d −1 with a median value of ~48% d −1 (see the summary table in Su et al 2007, and see Thomaz & Esteves 1997a,b, Törnblom & Søndergaard 1999, Carr et al 2005, Tao et al 2007 (Hyun et al 1998, Torréton et al 2002, Hyun & Kim 2003, Chen et al 2005, Hyun & Yang 2005, Gao et al 2007). Thus, while significant variability exists, median and mean turnover rates for the 2 types of community are very similar.…”
Section: Discussionmentioning
confidence: 99%
“…Biofilm turnover for environments -including decaying leaf litter, streams, mesocosm wetlands and tropical coastal lagoons -range from ~0.02 to 4000% d −1 with a median value of ~48% d −1 (see the summary table in Su et al 2007, and see Thomaz & Esteves 1997a,b, Törnblom & Søndergaard 1999, Carr et al 2005, Tao et al 2007 (Hyun et al 1998, Torréton et al 2002, Hyun & Kim 2003, Chen et al 2005, Hyun & Yang 2005, Gao et al 2007). Thus, while significant variability exists, median and mean turnover rates for the 2 types of community are very similar.…”
Section: Discussionmentioning
confidence: 99%
“…In some systems, high inputs of inorganic nutrients (nitrogen and phosphorus) may stimulate the growth of both microbial groups (Currie 1990, Brett et al 1999. Since, in nutrient-limited conditions, phytoplankton and bacterioplankton compete for nutrients, these relationships may therefore even be negative (Carr et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In some systems, high inputs of inorganic nutrients (nitrogen and phosphorus) may stimulate the growth of both microbial groups (Currie 1990, Brett et al 1999. Since, in nutrient-limited conditions, phytoplankton and bacterioplankton compete for nutrients, these relationships may therefore even be negative (Carr et al 2005).Predation is another factor that might affect the bacterioplankton-phytoplankton relationship, generally decoupling their dependence (Jeppesen et al 1997). Bacterial abundance is affected by predation by protozoans and metazoans (Pace et al 1990) and by viral infection (Fuhrman 1999), with different intensities depending on system type.…”
mentioning
confidence: 99%
“…Nutrient enrichment also affects the release of dissolved organic carbon (DOC) by algae by typically decreasing the fraction of primary production released as DOC (Fogg 1983). Although heterotrophic bacterial biomass rarely responds directly to elevated nutrients, many studies have found a positive relationship between algal and bacterial biomass within stream biofilms, which is usually attributed to the use of algal-released DOC by heterotrophic bacteria (Haack and McFeters 1982;Carr et al 2005). In pelagic systems, elevated nutrients have been shown to stimulate algal DOC exudation and subsequent bacterial production and respiration, but only during the late stages of blooms when algae become nutrient-limited (Norrman et al 1995; Van den Meersche et al 2004).…”
mentioning
confidence: 99%